Transnational feminism in film and media - Marciniak, Katarzyna, 1963-; Imre, Anikó; O'Healy, Áine. (New York : Palgrave Macmillan, 2007)
This collection of interdisciplinary essays examines current cinematic and media landscapes from the perspective of transnational feminist practices and methodologies. Focusing on film, media art, and video essays, the contributors chart innovative strategies for exploring contemporary visual cultures.
1. Screening unlivable lives: the cinema of borders / Imogen Tyler and Bruce Bennett -- 2. Border traffic: reimagining the voyage to Italy / Aine O'Healy -- 3. Cinema without frontiers: transnational women's filmmaking in Iran and Turkey / Asuman Suner -- 4. The refusal of reproduction: paradoxes of becoming-woman in transnational Moroccan filmmaking / Patricia Pisters -- 5. Enter freely, and of your own will: cinematic representations of post-socialist transnational journeys / Alice Mihaela Bardan -- 6. Womens resistance strategies in a high-tech multicultural Europe / Ginette Verstraete -- 7. Videographies of navigating geobodies / Ursula Biemann -- 8. Affective nationalism? and transnational post-communist lesbian visual activism / Aniko Imre -- 9. Long-legged girls and the transnational circuits of Vietnamese popular culture / Lan Duong -- 10. Palatable foreignness / Katarzyna Marciniak --11. Translating silences: a cinematic encounter with incommensurable difference / Priya Jaikumar -- 12. The abjection of patriarchy: Ibolya Fekete's Chico and the transnational feminist imaginary / Marguerite Waller.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Women in motion pictures; Feminism and motion pictures; English language